Extravesical Ureteral Reimplantation Following Lich-Gregoir Technique for the Correction of Vesico-Ureteral Reflux Retrospective Comparative Study Open vs. Laparoscopy - Bustangi, Nasir; Kallas Chemaly, Anthony; Scalabre, Aurelien; Khelif, Karim; Luyckx, Stéphane; Steyaert, Henri; Varlet, Francois; Lopez, Manuel (Frontiers in Pediatrics, 2018)
Introduction: The aim is to compare the outcome of open versus laparoscopic Lich-Gregoir technique in patients with vesicoureteral reflux. We report a retrospective multicenter comparative study between open and laparoscopic extra-vesical ureteral reimplantation (EVUR) following Lich-Gregoir (LG) technique for the correction of Vesico-Ureteral Reflux (VUR). Materials and Methods: Between January 2007 and December 2015, 96 patients with VUR (69 females and 27 males) and deterioration of the renal function, underwent EVUR following LG technique. Fifty patients (16 males and 34 females) were operated by open surgery (group A). The mean age was 4.22 years-old, (14–147 months). Laparoscopic approach (group B) was performed in 46 patients (11 males and 35 females). The mean age was 4.19 years-old (15–110 months). We compared the results in relation to degree of VUR, operative time, hospital stay, post-operative pain medications, recovery time, complications, successful rate, recurrence, and follow-up. Statistical analysis was done used Chi square test for categorical variables and the Student t-test for continuous variables. P < 0.05 was considered significant. Results: In both groups no correlation was identified between age or weight and operative time, length of stay or total analgesia used. The mean operative time for group A was 63.2 and 125.4 min for unilateral and bilateral VUR, respectively, and for the group B was 127.90 and 184.5 min, respectively. There was no conversion in the laparoscopic group. Perioperative mucosal perforation of the bladder occurred in 6 patients of group A and 4 patients of group B and was immediately repaired. One patient had to be reoperated for leakage in group B. The mean duration of Morphine, IV and PO analgesia was shorter in group B. The mean hospital stay was 5.46 days for group A and 1.54 days for Group B. The success rate was 98% in group A and 97, 8% in group B. The mean follow-up was 3.67 years for the open and 1.54 years for the laparoscopic group. Transitory voiding dysfunction occurred in bilateral EVUR in one case in each group. Conclusion: Laparoscopic or Open approach for the correction of VUR following Lich-Gregoir technique is effective in unilateral and bilateral VUR with similar results. Laparoscopic approach reduces significantly (p < 0.05 in each item) post-operative pain medication, hospital stay, and allows for a faster return to normal activity.